Cooper, Helen. 2023. The Canterbury Tales. Oxford Guides to Chaucer. 3rd ed. Oxford: Oxford University Press. Pp. xiii + 484. ISBN 978019882142. - Archibald, Elizabeth (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Cooper, Helen. 2023. The Canterbury Tales. Oxford Guides to Chaucer. 3rd ed. Oxford: Oxford University Press. Pp. xiii + 484. ISBN 978019882142.